Joint small‐angle X‐ray and neutron scattering data analysis of asymmetric lipid vesicles. Issue 2 (28th February 2017) - Eicher, Barbara; Heberle, Frederick A.; Marquardt, Drew; Rechberger, Gerald N.; Katsaras, John; Pabst, Georg
Abstract : Low‐ and high‐resolution scattering length density models for the joint analysis of small‐angle neutron and X‐ray scattering experiments on asymmetric lipid vesicles are presented. Abstract : Low‐ and high‐resolution models describing the internal transbilayer structure of asymmetric lipid vesicles have been developed. These models can be used for the joint analysis of small‐angle neutron and X‐ray scattering data. The models describe the underlying scattering length density/electron density profiles either in terms of slabs or through the so‐called scattering density profile, previously applied to symmetric lipid vesicles. Both models yield structural details of asymmetric membranes, such as the individual area per lipid, and the hydrocarbon thickness of the inner and outer bilayer leaflets. The scattering density profile model, however, comes at a cost of increased computational effort but results in greater structural resolution, showing a slightly lower packing of lipids in the outer bilayer leaflet of ∼120 nm diameter palmitoyloleoyl phosphatidylcholine (POPC) vesicles, compared to the inner leaflet. Analysis of asymmetric dipalmitoyl phosphatidylcholine/POPC vesicles did not reveal evidence of transbilayer coupling between the inner and outer leaflets at 323 K, i.e. above the melting transition temperature of the two lipids.